The impact of criticism time on its logical fallacy content in architectural design studio - Abdullah, Nahith Taha; Hameed, Areej Abdulrazaq (Sulaimani Journal for Engineering Sciences, 2019)
This paper attempts to shed light on a phenomenon that occurs in the discourse in general which is the logical fallacies, as it tries to project it on architecture criticism that take place inside design studio, as a type of discourse. It adopts an analytical approach considering criticism process as one of its basic elements, to test the main hypothesis which is the possibility of existance of some logical fallacies in criticism directed at students during that process the paper tries also to clarify the effect of design session time on the nature of these fallacies. The paper find some of these fallacies vary in number and type depending on the change of the monetary session it also find that the progress of sessions decrease count fallacies significantly to come out after the results and indicators from which to judge the practice of academic and contribute to its improvement and development.
Keywords: Design; Logical Fallacy; Architectural Education